Satisfaction of geriatric patients with neuromusculoskeletal conditions with the Feldenkrais method in physical medicine - Alvarado, Mitchell Walter Carbajal (Edelweiss Applied Science and Technology, 2025)
The satisfaction of geriatric patients requires evaluative dimensions to measure health services in the field of physical medicine or the area to be treated, since satisfaction instruments are adapted to individual particularities and the methods applied according to their pathology. To determine satisfaction with the Feldenkrais method in geriatric patients with neuromusculoskeletal diseases in physical medicine, an observational, cross-sectional, and descriptive study was conducted. Perception of satisfaction with the Feldenkrais method was measured using a custom instrument with a sample of 100 geriatric patients, both men and women, from a physical rehabilitation center, and under informed consent. A questionnaire with 20 items across 3 dimensions was applied. The average score was 68.29; the median was 68, and the mode was 65, with a standard deviation of ±8.55. The predominant sex was 60% women, and the most common age group was 60 to 69 years old. Regarding diseases, 25% presented scoliosis, and a lower percentage had Parkinson's disease and herniated discs, each at 5%. In the HUMAN dimension, 65% of patients were very satisfied, and 35% were satisfied. In the SCIENTIFIC dimension, 55% of patients were satisfied, 35% very satisfied, and 10% indifferent. In the ENVIRONMENT dimension, 55% of patients were satisfied, 40% very satisfied, and 5% indifferent. Overall, 55% of geriatric patients were satisfied with the Feldenkrais method, and 45% were very satisfied with their treatment. These studies underscore the urgent need for systems to incorporate new, evidence-based methodologies into their treatments, promoting the combination of clinical applications of physical rehabilitation and innovation as pillars of health treatments that transcend classical medicine and now challenge more distant areas such as quantum physics, the effect of vibrational waves, and other principles. This leads to a new era of universal physics in human rehabilitation and its benefits in medicine.